10. Neurophysiological prognosis in comatose patients after cardiac arrest: The Italian Multicentric Study (ProNeCA). Issue 12 (December 2017) - Grippo, A.; Carrai, R.; Audenino, D.; Callegarin, C.; Celani, M.G.; Lombardi, M.; Marrelli, A.; Mecarelli, O.; Minardi, C.; Minicucci, F.; Motti, L.; Politini, L.; et al.
Abstract : To evaluate the prognostic value of EEG and SEPs association in post-anoxic comatose patients at different recording time from cardiac arrest (CA) with a prospectic multicentre study. Twelve hospitals participated to the study. EEG and SEPs were recorded within 12, 24, and at 72 hs after CA. EEG was classified into "non-continuous" and "continuous". SEPs were dichotomized into "bilaterally absent" (BA) and "present". Neurologic outcome was evaluated at 6 months by Cerebral Performance Category. Among the 392 patients admitted after CA in the 11 hospitals 298 where enrolled. Within 12 h (120 patients) after CA, continuous EEG predicted good outcome and BA SEPs predicted poor outcome. Continuous EEG and BA-SEPs were never found in the same patient. At 48–72 h after CA (142 patients) both grade 2 EEG and BA-SEPs predicted poor outcome. The combination of EEG/SEP findings allows prediction of good and poor outcome (within 12 h after CA) and of poor outcome (after 48–72 h). Recording of EEG and SEPs in the same patients allows always an increase in the number of cases correctly classified, and an increase of the reliability of prognostication in a single patient due to concordance of patterns.